2010
DOI: 10.12693/aphyspola.117.423
|View full text |Cite
|
Sign up to set email alerts
|

AFM, XRD and HRTEM Studies οf Annealed FePd Thin Films

Abstract: Ferromagnetic FePd L10 ordered alloys are highly expected as forthcoming high-density recording materials, because they reveal a large perpendicular magnetocrystalline anisotropy [1]. The value of the magnetic anisotropy of FePd alloy strongly depends on the alloy composition, degree of alloy order as well as on the crystallographic grain orientation. In particular, to obtain the perpendicular anisotropy, it is necessary to get the films with (001) texture. One of the successful methods, which allows one to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…The experimental observations suggest that Au diffusion outruns relaxation of the Ni film and, therefore, forms a predominant Au/SiO 2 interface. Surprisingly, no remaining Au absorption layers on top of 14 agglomerated Ni grains were detected by either EDXS elemental mapping or atomic resolution HAADF-STEM imaging.…”
Section: Film Morphology At the Early Stages Of Dewettingmentioning
confidence: 97%
See 2 more Smart Citations
“…The experimental observations suggest that Au diffusion outruns relaxation of the Ni film and, therefore, forms a predominant Au/SiO 2 interface. Surprisingly, no remaining Au absorption layers on top of 14 agglomerated Ni grains were detected by either EDXS elemental mapping or atomic resolution HAADF-STEM imaging.…”
Section: Film Morphology At the Early Stages Of Dewettingmentioning
confidence: 97%
“…Once a hole in the film has formed, it will grow subsequently by continuous diffusion exposing the free surface of the underlying substrates [9]. Wetting-dewetting transitions have been extensively studied in single component films, but only few studies are reported for multi-component films [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning, that the model does not take into account the temperature dependencies of the material properties such as absorption, density, specific heat and thermal conductivity, and assumes, that between laser pulses they do not change. The peak temperature of 500 circ C was chosen basing on results of our previous investigations, [9,11,12] which showed that it is the minimum temperature required to induce a diffusion process, and to start transformation from multilayer system into ordered alloy.…”
Section: Pulsed Laser Annealingmentioning
confidence: 99%
“…• C. Usually such annealing temperature is sufficient [9,10] to fabricate the chemically ordered L1 0 alloy, but is not large enough to produce the alloy with a (001) texture, which is needed to obtain perpendicular magnetic anisotropy. To reduce the temperature of L1 0 structure formation and to induce (001) texture the FePd alloy was doped with Cu, as it was observed in our previous studies.…”
Section: Introductionmentioning
confidence: 99%